Characterization of a site-specific restriction endonuclease from Rhodopseudomonas sphaeroides. - Lynn, S P (1979)
A type II restriction endonuclease, RshI, has been partially purified from photoheterotrophically grown Rhodopseudomonas sphaeroides strain 2.4.1. The enzyme preparation, after a single DE-52 column fractionation, is free of 5' exonuclease and phosphatase activities but contains a trace of 3' exonuclease activity. Based upon deoxyribonucleic acid (DNA) sequencing data in the vicinity of the enzyme-promoted cleavage of pBR322 DNA, we have concluded that RshI probably recognizes the palinodromic hexanucleotide sequence 5'-CGATCG-3' and cleaves between the T and C. lambda cI857 DNA contains three RshI sites, two of which lie in the replaceable region. The plasmid pBR322, which carries resistances to ampicillin and tetracycline, contains a single RshI site in the ampicillin resistance determinant. Insertion of DNA into the RshI site of pBR322 results in loss of ampicillin resistance but retention of tetracycline resistance, thereby providing a convenient screening procedure for recombinant plasmids.